Pendampingan Standarisasi Guru Taman Pendidikan Al-Qur`an Melalui Pelatihan Metode Tilawati Berbasis Aset - Fathurrahmah, Nurulli; Amin, Moh; Shinwanudin, M (Janaka, Jurnal Pengabdian Masyarakat, 2020)
A teacher of the Qur'an Education is required to determine the right method of learning the Qur'an. In addition, it takes skill and skill that is standard in implementing Qur'anic learning. Therefore, it is necessary to mentoring the standardization of Qur'anic learning through training, among other trainings in Tilawati method. This mentoring is done by the asset approach in the framework of Asset-based-Community Development (ABCD). Performance Achievement in this mentoring is the empowerment of religious leaders and society in providing accommodation and consumption. Community assets were successfully empowered to support the program's success.